Executive Function and Social Media Addiction in Female College Students: The Mediating Role of Affective State and Stress. Issue 4 (20th June 2022) - He, Zhonghua; Li, Mingde
Abstract: Social media addiction is the emerging occurrence in which individuals develop psychological dependencies on microblog, wechat, Tik Tok and so on. Existing research has demonstrated the possible relationship between mobile social media addiction and disordered eating attitudes/behavior. In this study, we investigated the relationship between executive function, especially food-inhibitory control, affective state/stress, and mobile social media addiction among female college students as all play predictive roles in food addiction. A structural equation model was used to examine the mediation model hypothesis, and the results confirmed the mediating role of affective state and stress between executive function, especially inhibitory control over high-calorie food, and mobile social media addiction among Chinese female college students. The results verify the correlation between social media addiction and disordered eating attitudes/behavior from the perspective of psychological mechanisms. These proposals emphasize the significance of improving inhibitory control over high-calorie food and the importance of providing psychological counseling to intervene in negative emotions and stress management in female college students.